Simulation tool for learning signals and systems theory - part A - Tay, Pang Hing (Nanyang Technological University, 2022)
Simulation Tool for Learning Signals and Systems Theory – Part A is a Matlab based simulation software that as the name implies will help users learn signal and systems theory through simulation. There is a lack of such a simulation software in the market, and so this Final Year Project was conceived to fill in that gap. This report will go through the design process, code and simulation results, and will explain some of the short comings faced in this simulation software and what work could be done in the future.